2006
DOI: 10.1016/j.psychsport.2005.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Perceived motivational climate, need satisfaction and indices of well-being in team sports: A longitudinal perspective

Abstract: Link to publication on Research at Birmingham portal General rights Unless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law. • Users may freely distribute the URL that is used to identify this publication. • Users may download and/or print one copy of the publication from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

36
301
6
53

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 372 publications
(410 citation statements)
references
References 30 publications
36
301
6
53
Order By: Relevance
“…The responses are rated on a 7-point Likert scale ranging from 1 (not at all true) to 7 (very true). Previous research has confirmed the reliability of this instrument (Balaguer et al, 2008;Reinboth & Duda, 2006).…”
Section: Instrumentsmentioning
confidence: 54%
“…The responses are rated on a 7-point Likert scale ranging from 1 (not at all true) to 7 (very true). Previous research has confirmed the reliability of this instrument (Balaguer et al, 2008;Reinboth & Duda, 2006).…”
Section: Instrumentsmentioning
confidence: 54%
“…Percebe-se que há consenso entre os pesquisadores com relação à importância da saúde, enquanto um fator motivacional determinante. (GRAÇA; BENTO, 1993;CAPOZZOLI, 2006;GUEDES, 1998;RYAN;DECI, 2000a;REINBOTH;DUDA, 2005).…”
Section: Comparações De Media Entre Os Gruposunclassified
“…Diferentes estudios en el contexto deportivo han demostrado que un clima que implica a la tarea predice la satisfacción de las necesidades psicológica básicas (Almagro, Sáenz-López, González-Cutre, y Moreno-Murcia, 2011;Reinboth y Duda, 2006). Además, tal y como establece la teoría de la autodeterminación (Deci y Ryan, 1985; la satisfacción de las necesidades psicológicas producirá un aumento en la motivación intrínseca.…”
Section: Introductionunclassified